ANALISIS SEMIOTIK RIFFATERRE PADA SYAIR LAGU MAN ANĀ KARYA AL-IMAM AL-HABIB UMAR MUHDHOR BIN ABDURRAHMAN ASSEGAF - Faizetul Ukhrawiyah; Fauziyah Kurniawati (Haluan Sastra Budaya, 2021)
This research aims to elaborate the meaning of message contained in lyrics of song entitled Man Anā by al-Imam al-Habib Umar Muhdhor bin Abdurrahman Assegaf based on semiotic analysis by Michael Riffaterre. This research is descriptive qualitative research. To collect data, researchers use reading and noting technique. Then to analyze data, researchers use Miles and Huberman model. The results of this research reveal that the lyrics of song entitled Man Anā in heuristic reading have scattered meanings and unified ideas. In hermeneutic reading, the potential hypogram produces the meaning of "I" expressing love and respect for "you" figure. The model in lyrics of this song is sentence man anā man anā laulākum and kaifa mā ḥubbukum kaifa mā ahwākum. This model produces a poetry matrix, which is about the position of teacher in front of students. The actual hypogram which became the background for the formation of this matrix is the words of Sayyidina Ali bin Abi Talib r.a. that there are six things that become provisions for a student to gain knowledge in learning, one of which is teacher guidance. So it is appropriate for a student to give great love and respect to his teacher.